Mega-Events and Legacies in Post-Metropolitan Spaces Expos and Urban Agendas - Di Vita, Stefano (Mega Event Planning,, 2018)
This book offers new perspectives through which to observe and interpret mega-events. Using the specific case studies of World's Fairs, Di Vita and Morandi present a report of the Milan Expo 2015 and its trans-scalar legacies. While the event and post-event have been affected by the world crisis, the locations of exhibition areas have greatly expanded, encompassing regional as well as post-metropolitan spaces. The two main aims of comparing Milan to previous expos such as Lisbon 1998, Zaragoza 2008 and Shanghai 2010, were to demonstrate the contribution of the 2015 World's Fair to the urban innovation process and to the debate surrounding a new urban agenda; as well as to examine empirically and theoretically the international discussion regarding the growth of regional and macro-regional scales of contemporary cities in order to offer suggestions for future urban agendas through mega-events. This book will be of great value to students, researchers and policy makers in the area of urban planning and the urban studies more broadly, geography and spatial politics. .